(untitled) (Journal of the College of Basic Education, 2023)
Education development plans in various developed and developing countries of the world alikeWhether a great interest in overcoming his problems, raising his efficiency, and advancing the level of professional performancegraduates. This interest is due to a fundamental factor, which is the scientific and technical revolution and the competition of countries.Therefore, it has become necessary for vocational preparation to take new forms.After it has become an essential pillar in preparing each individual according to the nature of his specialization.Physical education needs integrated leaders who are able to useKinetic activities in achieving the educational goals of contemporary society, and for thatThere have been spread all over the world institutes and colleges of physical education aimed at preparing leadersPhysical education through specialized curricula that qualifies the graduate to perform many tasks.And the responsibilities that meet the needs of society on the one hand and achieve the goals of physical education on the other hand.another side. The faculties of physical education mainly aim at preparing teachers for education.sports for the intermediate and preparatory stages, and therefore the content of the curriculum is directed to teaching